(untitled) (Az-Zaida: Jurnal Ilmu Multidisiplin, 2026)
Students’ understanding of fiqh in Islamic boarding schools is not solely determined by formal instructional methods, but is also significantly influenced by the dormitory environment as a social, spiritual, and academic space. This study aims to investigate the extent to which the dormitory environment contributes to students’ comprehension of fiqh through the learning of the classical Islamic legal text Kifayatul Akhyar. The research employed a qualitative approach using a case study design, conducted at the Female Dormitory of Madrasah Aliyah Nurul Jadid’s Religious Studies Program (MANJ-PK). The findings reveal that the dynamics of the dormitory foster a strong learning culture for classical Islamic texts through intense social interaction, daily spiritual reinforcement, and the habituation of religious practices that facilitate the internalization of fiqh values. Instructional strategies used include the talaqqi method, peer group discussions, and personal mentoring, all of which enhance students’ understanding of the text. Documentation of religious activities indicates a direct impact of fiqh understanding on students’ religious behavior, both in worship and in social relations. These findings highlight the vital role of the dormitory as a transformative and contextual educational setting for applied fiqh learning.